2021
DOI: 10.1186/s12954-021-00522-3
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to use a wearable device capable of detecting and reversing overdose among people who use opioids in Philadelphia

Abstract: Background The incidence of opioid-related overdose deaths has been rising for 30 years and has been further exacerbated amidst the COVID-19 pandemic. Naloxone can reverse opioid overdose, lower death rates, and enable a transition to medication for opioid use disorder. Though current formulations for community use of naloxone have been shown to be safe and effective public health interventions, they rely on bystander presence. We sought to understand the preferences and minimum necessary condi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 26 publications
(37 reference statements)
3
48
0
1
Order By: Relevance
“…Numerous individual-level factors are known to impact the acceptability of wearable sensor-based health interventions, including cognitive ability, social characteristics, technical knowledge, and cultural norms (23)(24)(25)(26)(27). Within the SUD treatment space, our work and other investigators have found generally high acceptability among individuals who are actively using drugs (including cocaine and opioids) and those in recovery from SUDs (28)(29)(30). However understanding the specific factors that impact usability and create barriers to use will be critical: user experience, specifically stigma and device discreetness need to be evaluated in the target populations under unsupervised conditions to determine feasibility of device deployment.…”
Section: Introductionmentioning
confidence: 69%
“…Numerous individual-level factors are known to impact the acceptability of wearable sensor-based health interventions, including cognitive ability, social characteristics, technical knowledge, and cultural norms (23)(24)(25)(26)(27). Within the SUD treatment space, our work and other investigators have found generally high acceptability among individuals who are actively using drugs (including cocaine and opioids) and those in recovery from SUDs (28)(29)(30). However understanding the specific factors that impact usability and create barriers to use will be critical: user experience, specifically stigma and device discreetness need to be evaluated in the target populations under unsupervised conditions to determine feasibility of device deployment.…”
Section: Introductionmentioning
confidence: 69%
“…We classified technologies into 3 main groups according to their main function, namely, “OD alert,” “OD response,” and “combined OD alert and response.” These are shown in Tables 1 - 3 . Multimedia Appendix 2 [ 24 - 38 , 40 - 47 ] displays more detailed information about each study (ie, intervention, function, focus, device, theme, and study design). Although there is frequently a degree of overlap between the first 2 groups, as all devices ultimately need to combine OD alert and response, this classification is based on the main focus of the study.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the studies we identified are in the prototype phase and are more focused on the antidote dispenser than on the sensor. A total of 9% (1/11) of the studies simply suggested such a device as a concept to assess its acceptability in a survey [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Opioid overdoses can be reversed rapidly with naloxone, a drug that is widely available to emergency medical services (EMS) and increasingly the general public. However, up to 51.8% of fatal overdoses occur when the person is alone, and in 27.4% of cases bystanders do not recognize the symptoms of an overdose and are not able to react in a timely manner 28 . Additionally, EMS may not always be able to respond promptly if the overdosed patient is in a less accessible location, such as in rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent human factor studies are needed to assess the comfort and discreetness of the device when worn for longer periods of time, particularly in unsupervised settings. In a recent study 28 involving 97 adults with an opioid-use history of at least three months 76% of participants were willing to wear a closed-loop device for sensing an overdose and delivering a reversal agent upon detection. Almost all (75.5%) respondents indicated a willingness to wear the device all or most of the time.…”
Section: Discussionmentioning
confidence: 99%